13C-n.m.r. of the cyanylated apoflavodoxin and flavodoxin from Clostridium pasteurianum. - Doherty, G M (1993)
The thiol group of the flavodoxin from Clostridium pasteurianum has been cyanylated in a single step using [cyanato-13C]2-nitro-5-thiocyanatobenzoic acid. This chemical modification increases the dissociation constant of the apoflavodoxin-FMN complex 10-fold from 0.33 +/- 0.15 nM to 2.9 +/- 1.3 nM. The thiocyanate carbons of the cyanylated cysteine residue of apoflavodoxin and flavodoxin had chemical shift values of 114.7 and 112.3 p.p.m. respectively. From these chemical shifts we conclude that the binding of FMN by the cyanylated apoflavodoxin causes a decrease in the polarity and/or hydrogen bonding capacity of the environment of the thiocyanate group. We compare these results with those obtained from similar studies on the cyanylated apoflavodoxin and flavodoxin from Megasphaera elsdenii and we discuss how FMN binding and cyanylation perturb the structures of apoflavodoxins from Megasphaera elsdenii and Clostridium pasteurianum.